Southern Ocean Calcification Controls the Global Distribution of Alkalinity. Issue 12 (1st December 2020) - Krumhardt, K. M.; Long, M. C.; Lindsay, K.; Levy, M. N.
Abstract : Biological processes in Southern Ocean surface waters have widespread impacts on global productivity and oceanic CO2 storage. Here, we demonstrate that biological calcification in the Southern Ocean exerts a strong control on the global distribution of alkalinity. The signature of Southern Ocean calcification is evident in observations as a depletion of potential alkalinity within portions of Subantarctic Mode and Intermediate Water. Experiments with an ocean general circulation model indicate that calcification and subsequent sinking of biogenic carbonate in this region effectively transfers alkalinity between the upper and lower cells of the meridional overturning circulation. Southern Ocean calcification traps alkalinity in the deep ocean; decreasing calcification permits more alkalinity to leak out from the Southern Ocean, yielding increased alkalinity in the upper cell and low‐latitude surface waters. These processes have implications for atmosphere‐ocean partitioning of carbon. Reductions in Southern Ocean calcification increase the buffer capacity of surface waters globally, thereby enhancing the ocean's ability to absorb carbon from the atmosphere. This study highlights the critical role of Southern Ocean calcification in determining global alkalinity distributions, demonstrating that changes in this process have the potential for widespread consequences impacting air‐sea partitioning of CO2 . Plain Language Summary: Plankton living in the Southern Ocean affect the composition of seawater through biological processes. Due to the particular oceanic circulation in the Southern Ocean, these biologically driven changes in ocean chemistry can have widespread effects on the global ocean. Species of plankton that form shells of calcium carbonate remove alkalinity from surface waters through the process of calcification. The amount of alkalinity in surface waters is important because it affects how much CO2 the ocean can absorb from the atmosphere. We show that Southern Ocean calcifying plankton affect the global distribution of alkalinity through the presence of a Southern Ocean "alkalinity trap." More Southern Ocean calcification yields a stronger alkalinity trap, with more alkalinity being retained in the Southern Ocean and in deep waters, away from the atmosphere. Reduced calcification in the Southern Ocean permits more alkalinity to escape the Southern Ocean and remain in the upper ocean globally. These changes affect oceanic CO2 uptake from the atmosphere. Key Points: Calcification in the Southern Ocean affects the global distribution of alkalinity Changes in Southern Ocean calcification affect how the ocean absorbs atmospheric carbon dioxide Southern Ocean calcium carbonate fluxes control the strength of the Southern Ocean alkalinity trap